2012
DOI: 10.1289/ehp.1205412
|View full text |Cite|
|
Sign up to set email alerts
|

450K Epigenome-Wide Scan Identifies Differential DNA Methylation in Newborns Related to Maternal Smoking during Pregnancy

Abstract: Background: Epigenetic modifications, such as DNA methylation, due to in utero exposures may play a critical role in early programming for childhood and adult illness. Maternal smoking is a major risk factor for multiple adverse health outcomes in children, but the underlying mechanisms are unclear.Objective: We investigated epigenome-wide methylation in cord blood of newborns in relation to maternal smoking during pregnancy.Methods: We examined maternal plasma cotinine (an objective biomarker of smoking) meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

59
654
5
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 661 publications
(724 citation statements)
references
References 38 publications
59
654
5
6
Order By: Relevance
“…However, close inspection of the data in Joubert et al revealed that 1 of the 4 differentially methylated CpG sites was more highly methylated among infants whose mothers were smokers. 12 Additionally, the magnitude of AHRR DNA methylation difference between mothers with undetectable vs. high cotinine levels at each of their 4 significant sites was of similar magnitude (»4%) as associations with our categorical predictors (2-3%). We did not analyze the same CpG sites as the smoking-associated CpG sites reported in prior studies but instead chose to maximize the CpG sites in the AHRR promoter region that our pyrosequencing assay would capture.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…However, close inspection of the data in Joubert et al revealed that 1 of the 4 differentially methylated CpG sites was more highly methylated among infants whose mothers were smokers. 12 Additionally, the magnitude of AHRR DNA methylation difference between mothers with undetectable vs. high cotinine levels at each of their 4 significant sites was of similar magnitude (»4%) as associations with our categorical predictors (2-3%). We did not analyze the same CpG sites as the smoking-associated CpG sites reported in prior studies but instead chose to maximize the CpG sites in the AHRR promoter region that our pyrosequencing assay would capture.…”
Section: Discussionsupporting
confidence: 50%
“…13 Others have demonstrated that these same methylation sites differed in the offspring of women who smoked during pregnancy, compared to offspring of non-smokers. 12,28 Prior studies demonstrating associations between smoking and AHRR DNA methylation used epigenome-wide methylation assays designed to discover previously unknown associations. 12,13 Given the results of these prior studies demonstrating that AHRR DNA methylation is modifiable during pregnancy, 12 we chose AHRR as a candidate gene to conduct a hypothesis-driven study of perinatal predictors of AHRR DNA methylation in cord blood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This balance of responsiveness to stimuli and heritability results in a unique mechanism for lasting signatures of prior exposures that accumulate over the lifetime (Cortessis et al ., 2012; Feil & Fraga, 2012). As an example of a specific exposure that has been shown to leave a lasting signature, cigarette smoke has been linked to changes in DNA methylation at the AHRR locus both in smokers and in children of smokers (Saxonov et al ., 2006; Monick et al ., 2012; Joubert et al ., 2012; Shenker et al ., 2013; Sun et al ., 2013 Elliott et al ., 2014; Lee et al ., 2015; Shah et al ., 2014). Smoking‐associated DNA methylation changes have also been found in genes involved in inflammatory networks, important candidates in the risk of age‐related diseases such as heart disease and stroke (Breitling et al ., 2012; Dogan et al ., 2014).…”
Section: Epigenetic Drift Vs the Epigenetic Clock: Two Phenomena Undmentioning
confidence: 99%
“…Several studies have investigated the epigenome-wide association between smoking, an important PM source, and DNA methylation. Using the 450K platform and Bonferroni correction, Joubert et al 17 identified 26 CpGs with methylation changes in newborns related to maternal smoking during pregnancy in a large Norwegian birth cohort. Specifically, the authors documented changes at CpGs in cytochrome p450 1A1 (CYP1A1) and aryl-hydrocarbon receptor repressor (AHRR), genes known to play a key role in the aryl hydrocarbon receptor (AhR) signaling pathway that mediates the detoxification of components of tobacco smoke.…”
Section: Introductionmentioning
confidence: 99%